Analysis of Institutional and Sustainability Eha Laut and Mane’e as Community Based Coastal Resource Management - ., Khoirunnisak; Satria, Arif (Sodality: Jurnal Sosiologi Pedesaan, 2016)
ABSTRACTEha is the rule managing the harvest of crops both from marine and terrestrial. Mane’e is the fish harvest ceremony using sammi ropes after one year period of the Eha Laut. Both traditions have been carried out since immemorial time as an attempt to keep the preservation of natural resources and accustom people to live together. This study aimed to analyze the institutional elements of Eha Laut and Mane’e, the Eha Laut and Mane’e sustainability level in community-based coastal resources management. Based on this research, it is known that the performance of the Eha Laut and Mane’e in coastal resource management has been effective and run well. However, there are 3 (three) indicators which are still in the low level management. They are people’s participation in the local management, conflict resolution mechanisms and networks with external agencies. The Eha Laut and Mane’e sustainability level includes in the category of perfection. The level of sustainability assessed in three dimensions; economic, social and environmental dimensions. Dimension that needs more attention is the environmental dimension.Keywords: sustainable, institutional, community, coastal resources managementABSTRAKEha adalah aturan pengelolaan panen tanaman baik dari laut dan darat. Mane’e adalah upacara panen ikan menggunakan tali sammi setelah periode satu tahun Eha Laut. Kedua tradisi telah dilakukan sejak zaman dahulu sebagai upaya untuk menjaga kelestarian sumber daya alam dan orang membiasakan untuk hidup bersama. Penelitian ini bertujuan untuk menganalisis unsur-unsur kelembagaan Eha Laut dan Mane’e, yang Eha Laut dan Mane’e tingkat keberlanjutan dalam pengelolaan sumber daya pesisir berbasis masyarakat. Berdasarkan hasil penelitian, diketahui bahwa kinerja Eha Laut dan Mane’e dalam pengelolaan sumber daya pesisir telah efektif dan berjalan dengan baik. Namun, ada 3 (tiga) indikator yang masih dalam manajemen tingkat rendah. Mereka adalah partisipasi masyarakat dalam pengelolaan lokal, mekanisme resolusi konflik dan jaringan dengan lembaga-lembaga eksternal. The Eha Laut dan Mane’e tingkat keberlanjutan termasuk dalam kategori kesempurnaan. Tingkat keberlanjutan dinilai dalam tiga dimensi; ekonomi, sosial dan lingkungan dimensi. Dimensi yang perlu perhatian lebih adalah dimensi lingkungan.Kata kunci: berkelanjutan, kelembagaan, masyarakat, pengelolaan sumber daya pesisir.